Angiotensin converting enzyme insertion/deletion gene polymorphism: an observational study among diabetic hypertensive subjects in Malaysia - Jayapalan, J.J.; Muniandy, S.; Pheng, C.S. (Pharmacotherapy Group, University of Benin, Benin City, 2010)
Purpose: This study investigated the influence of angiotensin-1 converting enzyme (ACE) insertion-deletion (ID) gene polymorphism on the treatment responses of type 2 diabetic subjects at varying stages of nephropathy to ACE inhibitors (ACEI) with regard to blood pressure (MAP) and renal response (GFR). Methods: The pharmacological effect of ACE inhibition on mean arterial pressure (MAP) and glomerular filtration rate (GFR) were observed among a total of 62 subjects for a short-term duration of 15 months. MAP and GFR were calculated by standard mathematical formulae while the ACE ID genotype was determined using triple primer PCR. The general linear model repeated measures were applied to study the modulation of ACE inhibition on these parameters. Results: ACE ID genotyping of the 62 subjects showed that 19 (30.6 %) subjects had the II genotype, while 35 (56.4 %) subjects showed ID genotype and 8 (12.9 %) subjects had the DD genotype. Significant mean MAP reduction (p < 0.05) and null mean GFR changes (p > 0.05) from baseline values were observed among the subjects following antihypertensive treatment. However, when stratified according to ACE genotypes, no significant mean MAP and GFR changes were observed between genotypes following antihypertensive treatment (p > 0.05). Conclusion: ACE ID gene polymorphism does not determine the treatment efficacy of ACE inhibitors in the Malaysian population.